2020
DOI: 10.1002/elps.202000174
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of a weakly conducting droplet under the influence of an alternating electric field

Abstract: We investigate the electrohydrodynamics of an initially spherical droplet under the influence of an external alternating electric field by conducting axisymmetric numerical simulations using a charge‐conservative volume‐of‐fluid based finite volume flow solver. The mean amplitude of shape oscillations of a droplet subjected to an alternating electric field for leaky dielectric fluids is similar to the steady‐state deformation under an equivalent root mean squared direct electric field for all possible electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Equivalently, and for simplicity, the electrostatic stresses can be turned into a body force, 2,25,26…”
Section: ■ Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equivalently, and for simplicity, the electrostatic stresses can be turned into a body force, 2,25,26…”
Section: ■ Governing Equationsmentioning
confidence: 99%
“…Numerical simulations of the dynamics of multiphase fluids coupled with electric fields open the door for a wide range of applications. For example, in microfluidic devices, by improving the manipulation of small amounts of liquid with the fine control that electronic devices allow. , Moreover, numerical simulations have the potential to inform the design of electrode arrays to induce specific and complex liquid and film morphologies both at fluid–fluid interfaces and for finite volumes of liquids on solids. ,, For this reason, several numerical methods have been implemented to study this interaction, for example, finite-element, , boundary-element, finite-volume, and spectral methods. , …”
Section: Introductionmentioning
confidence: 99%
“…Results show that a significant increase in the amplitude leads to spike formation and the interface ruptures at the top electrode. Sahu et al (2020) conducted an axisymmetric numerical simulations using a charge-conservative volume-of-fluid based finite volume flow solver to investigate droplet deformation under an external alternating electric filed. Their results showed that the mean amplitude of shape oscillations of a droplet subject to an alternating electric field may deviate from the steady-state deformation under an equivalent root-mean-squared direct electric field.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, the microfluidic devices usher an ideal platform to study the rheological behavior of fluids because they are low-cost, portable, employ small amount of materials, and provide greater control on flow of materials under various forces [33][34][35][36]. A number of recent attempts employ microfluidic devices for the measurement of various mechanical properties of the materials [37].…”
Section: Introductionmentioning
confidence: 99%